Radiation-induced fibrosarcoma after breast-conserving therapy for breast cancer: a case report and literature review - Hideko Hoshina; Kouichi Kubouchi; Yutaka Tsutsumi; Hiroyuki Takei (Surgical Case Reports, 2023)
Abstract Background Radiation-induced sarcoma (RIS) has a 10-year incidence of 0.2–0.27% and a poor prognosis, although the radiation should need for breast-conserving surgery. In particular, radiation-induced fibrosarcoma has been rarer, and its incidence is 2.6–3.7% of RIS. Case presentation A 43-year-old woman with pT1N1M0 breast cancer underwent breast-conserving surgery, chemotherapy, radiation therapy 8 years ago, and continued hormonal therapy. She complained of a hard unprotruded mass palpated in her right upper outer quadrant of breast. Although we suspected local recurrence, core needle biopsy revealed atypical spindled tumor cells without mammary or epithelial markers. A diagnosis of fibrosarcoma was made via tumorectomy. She underwent additional enlarged surgery. Conclusions We report a rare case of fibrosarcoma in breast after breast-conserving surgery and radiation therapy. Fibrosarcoma after radiation therapy for breast cancer has been reported in 30 cases, including the present case. The dead and alive cases were not significantly different in terms of age, primary breast cancer, radiation dose, and following months. Patients with breast masses after radiation therapy should be suspected local recurrence and RIS.